Etiology of persistent mathematics difficulties from childhood to adolescence following very preterm birth. Issue 1 (2nd January 2022) - Clayton, Sarah; Simms, Victoria; Cragg, Lucy; Gilmore, Camilla; Marlow, Neil; Spong, Rebecca; Johnson, Samantha
ABSTRACT: Children born very preterm (VP; <32 weeks' gestation) have poorer mathematics achievement than term-born peers. This study aimed to determine whether VP children's mathematics difficulties persist from primary to secondary school and to explore the nature of mathematics difficulties in adolescence. For this study, 127 VP and 95 term-born adolescents were assessed at age 11–15 years. Mathematics achievement was assessed using the Wechsler Individual Achievement Test-II. Specific mathematics skills and general cognitive skills were assessed using standardized and experimental tests. VP adolescents had poorer mathematics achievement than term-born adolescents (−10.95 points; 95% CI −16.18, −5.73) and poorer number fact knowledge, understanding of arithmetic concepts, written arithmetic, counting, reading and writing large numbers, and algebra. Between-group differences in mathematics skills were no longer significant when working memory and visuospatial skills were controlled for ( p 's >0.05), with the exception of writing large numbers and conceptual understanding of arithmetic. In a previous study, 83 of the VP adolescents and 49 of the term-born adolescents were assessed at age 8–10 years using measures of the same skills. Amongst these, the between-group difference in mathematics achievement remained stable over time. This study extends findings of a persistent deficit in mathematics achievement among VP children over the primary and secondary school years, and provides evidence of a deficit in factual, procedural and conceptual mathematics skills and in higher order mathematical operations among VP adolescents. We provide further evidence that VP children's mathematics difficulties are driven by deficits in domain-general rather than domain-specific cognitive skills.